Transcending adversity: resilience in volunteer firefighters. Issue 2 (8th December 2020) - Blaney, Leigh McCarley; Wilde, David; Hill, Rowena
Abstract : Purpose: The purpose of this paper is to present a theory of psychological resilience in volunteer firefighters. Design/methodology/approach: Using a constructivist grounded theory (CGT) approach, the qualitative study engaged a purposive sample of eight firefighters in Canada, conducted in-depth interviews and analysed the data using comparative methods. Findings: The results provided unique insights into resilience in firefighters and revealing resilience as multidimensional, complex, dynamic and contextual. Six core concepts interrelate to construct resilience: relationships, personal resources, meaning-making, leadership, culture and knowledge. Practical implications: The findings of this research offer a framework for practical integration of resilience theory into workplace health policy and practice. The theory was co-created with firefighters hence is contextually sound to this population, but applicable to other emergency and health services. Originality/value: Volunteer firefighters are under-represented in the literature, despite facing intermittent and frequently intense work-related stressors; this research begins to address the gap in the literature. As well, previous resilience theories have noted relationships between some components, but there is little evidence linking categories; this theory more patently represents the complex nature of resilience in volunteer firefighters.